2019
DOI: 10.12688/f1000research.20330.1
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in understanding frontotemporal degeneration

Abstract: Frontotemporal degeneration (FTD) is a heterogeneous spectrum of neurodegenerative disorders characterized by diverse clinical presentations, neuropathological characteristics, and underlying genetic causes. In the last few years, several advances in the knowledge of clinical and biological aspects have been accomplished and three major scenarios have emerged that will represent the core issues in the FTD scene over the next few years. Foremost, the development of cerebrospinal fluid and blood biomarkers as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 125 publications
1
11
0
1
Order By: Relevance
“…At least two studies have identified a link between SF TSG-6 levels and OA progression in human subjects [ 29 , 61 ], and others have demonstrated an increase in HC-HA complex formation in RA and in murine models of inflammatory arthritis [ 40 , 59 ]. Our finding that SF HA concentration and viscosity varied significantly between and among healthy and OA individuals supports the hypothesis that OA is a heterogenous disease that contains multiple endotypes that may progress differently and respond differently to various treatments [ 62 , 63 ].…”
Section: Discussionsupporting
confidence: 81%
“…At least two studies have identified a link between SF TSG-6 levels and OA progression in human subjects [ 29 , 61 ], and others have demonstrated an increase in HC-HA complex formation in RA and in murine models of inflammatory arthritis [ 40 , 59 ]. Our finding that SF HA concentration and viscosity varied significantly between and among healthy and OA individuals supports the hypothesis that OA is a heterogenous disease that contains multiple endotypes that may progress differently and respond differently to various treatments [ 62 , 63 ].…”
Section: Discussionsupporting
confidence: 81%
“…MTX is a first-line disease-modifying drug proposed for treating the inflammatory forms of arthritis [ 88 ]. Rheumatoid arthritis (RA) and osteoarthritis (OA) are one of the leading forms of arthritic diseases, causing global disability [ 89 ], where RA is a chronic autoimmune disease and OA has been considered as a load-bearing disease, with low-grade inflammation [ 90 , 91 , 92 ]. MTX is the initial preferred drug for rheumatic diseases and is considered to be the gold standard for treatment of RA, used for more than three decades [ 93 ], however, it has been also proposed for treating OA [ 94 ].…”
Section: Methotrexate-loaded Hydrogels For Arthritis Therapymentioning
confidence: 99%
“…3 The occurrence of associated motor symptoms, as in progressive supranuclear palsy (PSP), corticobasal syndrome (CBS) and motor neuron disease (FTD-MND), enriches the spectrum of FTDrelated disorders. 4 Common to all FTD clinical syndromes is the underlying frontotemporal lobar degeneration (FTLD) which can be classified according to the predominant constituent proteins of cellular inclusions. While until 2006 only FTLD-Tau was well characterized, the following discovery of TAR DNA binding protein 43 (TDP- 43) and FET family proteins within tau-negative, ubiquitin-positive inclusions of a vast majority of FTLD cases, led to the introduction, respectively, of FTLD-TDP and FTLD-FET neuropathology.…”
Section: Introductionmentioning
confidence: 99%
“… 3 The occurrence of associated motor symptoms, as in progressive supranuclear palsy (PSP), corticobasal syndrome (CBS) and motor neuron disease (FTD-MND), enriches the spectrum of FTD-related disorders. 4 …”
Section: Introductionmentioning
confidence: 99%